Children's sleep and health: A meta-review. (August 2019) - Matricciani, Lisa; Paquet, Catherine; Galland, Barbara; Short, Michelle; Olds, Tim
Summary: Sleep is essential for children's health and well-being. Characteristics of children's sleep such as sleep duration, timing, quality and variability are increasingly being associated with a wide range of health outcomes. The purpose of this study is to conduct a meta-review (systematic review of systematic reviews) to examine the relationship between sleep and health in children. A systematic search of four electronic databases (Medline, PsychInfo, Scopus, and Embase) was conducted to identify systematic reviews that examine the association between characteristics of children's sleep and health. Key findings, as well as areas in need of further research were synthesised descriptively. A total of 39 systematic reviews were identified for inclusion, covering areas of cognition, psychosocial health, cardiometabolic health, adiposity and other outcomes such as musculoskeletal pain. There is substantial and consistent evidence relating sleep duration to adiposity and emotional outcomes. The relationships between sleep quality and timing and blood lipids and glycaemic control merit further research. Links between sleep and metabolic syndrome in children appear to be weak and inconsistent. Key areas identified in need for further research included studies that objectively assess children's sleep and move beyond cross-sectional study designs and consider characteristics of sleep other than duration. It was also noted that covariates applied across studies varied considerably and the issue of residual confounding was raised in a number of reviews. Lastly, all reviews reported studies adopted a traditional approach of examining only one aspect of children's sleep. Systematic reviews support the notion that sleep is important for children's health. However, further studies that objectively assess sleep and consider characteristics of sleep other than duration and outcomes other than adiposity are needed. An understanding of sleep as a multidimensional construct and as a component of the 24-h d, is also needed to better understand the relationship between sleep and health in children.